Use of Zoom to Improve Learning Outcomes of Class V Students Theme 5 - Jasminah Jasminah (Universitas Sebelas Maret, 2020)
Teaching success is determined not only by the ability, motivation, and activeness of students in learning and the completeness of learning facilities / environments, it will also depend a lot on the ability of teachers to develop various teaching skills. In order to prevent a greater spread of Covid-19, the Minister of Education and Culture issued Circular Number 36962 / MPK.A / HK / 2020 so that all teaching and learning activities both in schools and in universities can be carried out using online learning methods (online). I use the Zoom application, so I can interact with students even though it's only in cyberspace, so the teacher's role is not lost. The advantage of the Zoom application compared to other applications is that this application can be accessed for free. With learning activities using the ZOOM application it is expected to improve the learning outcomes of class V SD Negeri Gentan 04. In this study we used a contributive causal research method. The results showed that the use of zoom can increase the minimum learning completeness, namely an increase of 20% in cycle 1 and up to 14% in cycle 2